3 + 4x - 3x = 4 Given
3 + (4x - 3x) = 4
3 + x = 4 Combine like terms
3 - 3 + x = 4 - 3
x = 1 Subtraction Property of Equality
Answer: A = 4400(1 + 0.0825 x 22)
Step-by-step explanation:
A = accumulated amount
P = original amount unloaded- $4400
r = rate - 8.25% = 0.0825
t = years = 22
= 4400(1 + 0.0825 x 22)
Answer:
A.) y = 0.4x^(2) + 3.4x + 4
Step-by-step explanation:
x = -5
y = -3
Answer:
D
Step-by-step explanation:
The sum of the 3 angles in a triangle = 180°, that is
∠ 1 + ∠ 2 + ∠ 3 = 180°
Given ∠ 1 + ∠ 2 = 134°, then
134° + ∠ 3 = 180° ( subtract 134° from 180° )
∠ 3 = 46° → D